2021
DOI: 10.3390/ijerph182111221
|View full text |Cite
|
Sign up to set email alerts
|

Why Workers Hesitate to Report Their Work-Related Musculoskeletal Symptoms: A Survey at a Korean Semiconductor Company

Abstract: Underreporting work-related musculoskeletal disorders (WRMSD) has been an issue in South Korea. The purpose of this survey was to figure out how many employees of a semiconductor and liquid crystal display company in South Korea experience WRMSDs and what the possible obstacles in reporting to the company are. A survey was developed with demographic questions, perceived WRMSD symptoms, and reasons for reporting or not reporting WRMSD. The survey was distributed via the company’s intranet to all employees (24,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
(28 reference statements)
1
11
0
Order By: Relevance
“…Our ndings showed that a substantial number of NAs with a WRMSD (84.4%) did not report it to their management. This gure is higher than reporting rates in previous studies that ranged from 21-74% [13,17,18,35,36]. WRMSD reporting to management was related to positive attitudes toward reporting, experience of witnessing the injury reporting of others, good safety climate, and not having WRMSDs resulting in changed of jobs, tasks, or work due to WRMSDs.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Our ndings showed that a substantial number of NAs with a WRMSD (84.4%) did not report it to their management. This gure is higher than reporting rates in previous studies that ranged from 21-74% [13,17,18,35,36]. WRMSD reporting to management was related to positive attitudes toward reporting, experience of witnessing the injury reporting of others, good safety climate, and not having WRMSDs resulting in changed of jobs, tasks, or work due to WRMSDs.…”
Section: Discussionmentioning
confidence: 54%
“…Markary et al (2007) found that the odds of nonreporting of needlestick injury reporting were 19.29 times higher among surgeons who were aware of injury by another person than those who were not [43]. In a study of workers a Korea semiconductor company, one of the reasons for not reporting of WRMSDs was that the workers had never seen injury reporting of others [17]. By witnessing other's experience, workers may gain speci c information or knowledge such as where, how, and to whom to report their work-related problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…musculoskeletal complaints are not captured). Common themes for this include: recordable injury definitions being too narrow [ 15 , 19 ], reliance upon medical attention being sought (and from the appropriate providers) [ 15 , 39 , 40 ], and fear of negative consequences [ 39 , 41 44 ]. The self-report OSTRC-O has shown to reduce underreporting by using broader recordable injury definitions, and removing reliance upon medical attention being sought [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 Research has indicated that work-related injuries in national statistics have been generally underreported and underestimated in the United States as well as in other countries. 3,[5][6][7][8][9][10] For example, the US Bureau of Labor Statistics conducts the Survey of Occupational Injuries and Illnesses (SOII) among a sample of employers, which serves as the primary data source for national statistics of nonfatal occupational injuries and illnesses. However, SOII is particularly limited in its ability to capture work-related illnesses that are slow to develop, such as cumulative MSDs.…”
mentioning
confidence: 99%